Optimasi Penjadwalan Light Rail Transit dan Teman Bus Koridor Terminal Plaju- Terminal Jakabaring - Okpatiasari, Puspania; Buchari, Erika; Agustien, Melawaty (Publikasi Penelitian Terapan dan Kebijakan, 2023)
Light Rail Transit (LRT) which has been operated since 2018 in Palembang City has Teman Bus as its feeder. Based on service condition, LRT has fix timetable on every its station but Teman bus does not have timetable. Teman Bus has not provided departure or arrival time on every its halte. This condition concludes that public transportation has lack of adequate service for passengers. Therefore, optimizing timetable scheduling of LRT and Teman Bus is required as one of efforts for improving good public transport facilities. This paper aimed creating simulation of Teman Bus timetable based on real condition with headway and trip time data distribution method with case study in 2021. In addition, Program Linear Method will be used for syncrhonizing Teman Bus timetable and existing Light Rail Transit timetable based on passenger’s behavior to minimize waiting time. The result shows that passengers need 27 second of waiting time while transferring from LRT station to Teman Bus Stop and 60 second of waiting time while transferring from Teman Bus Stop to LRT station.